Pemanfaatan Residu/Ampas Produksi Biogas dari Limbah Ternak (Bio-Slurry) sebagai Sumber Pupuk Organik - Yusmiati bppt; Bambang Singgih (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
Survey results show that the soil organic matter content is very low, i.e. less than 2% for paddy fields and about 2% for the fields. The decrease of soil organic matter content is thought to be caused by the way of agricultural cultivation that is less attention to the content of organic matter with the use of chemical fertilizers is very intensive. The use of organic fertilizer can be a solution to the problem. Bio-slurry generated from liquid biogas reactors tends to be semi-solid and has characteristics, which are light brown or green and tend to be dark; little or no gas bubbles content; odorless and insect less; textured sticky, tough, and not shiny. The bio-slurry composition consists of organic materials (18-27%) and inorganic materials (2-3%). The content of NPK (Nitrogen, Phosphorus and Potassium) in liquid bio-slurry consists of nitrogen (0.25%), phosphorus (0.13), and potassium (0.12%). While the content of NPK in dry (solid) bio-slurry consists of nitrogen (3.6%), phosphorus (1.8%), and potassium (3.6%). In addition, bio-slurry also contains other nutrients, namely amino acids, fatty acids, humic acid, vitamin B-12, auxin hormones, cytokines, antibiotics, and micronutrients such as iron (Fe), copper (Cu), zinc (Zn), manganese (Mn), and molybdenum (Mo). Benefits of bio-slurry is for organic fertilizer, bio-pesticide, biological fertilizer, plant growth regulator, animal feed, improving soil structure, increasing weed growth, increasing soil fertility and increasing soil microorganism activity.